Beyond the frontiers of inner space: The success story of Y.Bhg. Datuk Dr Mazlan Othman - Sharifah Azlina, Raja Kamal Pasmah, Ir. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org